Exploration of conceptual understanding and values in mathematics among prospective mathematics teachers - Ifada Novikasari; Lily Rahmawati; Noor Elebiary (UNION : Jurnal Ilmiah Pendidikan Matematika, 2024)
The study examines the relationship between understanding mathematical concepts and mathematical values among prospective teachers at a state university in Central Java. The research employed a qualitative approach with content analysis, involving a mathematical concept understanding test and in-depth interviews with students at high, medium, and low ability levels. The results show that students with high ability tend to possess strong mathematical values like accuracy, perseverance, and curiosity, which enable them to grasp complex mathematical concepts. In contrast, students with low ability struggle to comprehend basic mathematical concepts and often rely on rote calculation and formula use. The findings suggest that differentiated learning strategies are necessary to cater to the diverse levels of mathematical concept understanding among prospective teachers. Enhancing mathematical values can be a key factor in improving conceptual understanding in mathematics education.